De-colonizando saberes em Círculos Narrativos: uma experiência em escola da periferia de São Paulo - Carlos, Priscila Dias (2013)
This research focused on literacy as a way to question the civility, progress and modernity, through discourses of intellectuals and scholars of public policy in the educational field, throughout the twentieth century, focused on school integration of people ensnared in universes of matrices oral. Through the experience of Circles Narrative, bring to the surface tension between orality and literacy as cultural violence perpetrated by the school curriculum, without losing sight of acts of re-existence of youth peripheral municipality of São Paulo. Moreover, we raise issues related to education through performance and senses a "Pedagoginga" or education that consider popular knowledge, indicate paths for intercultural education